1991
DOI: 10.1177/097133369100300204
|View full text |Cite
|
Sign up to set email alerts
|

The Role of Psychology in the An alysis of Poverty: Some Suggestions

Abstract: The aim of this article is to draw together research findings in social and organisational psychology literature to illustrate that psychology has a role in helping eliminate poverty. Following an analysis of poverty similar to that of Mehryar (1984) which asserts that the cause and solution of poverty both are politico-economic, it is argued that certain psychological findings (relating to perceptions of poverty and the nature of institutional decision-making systems) may well aid such a struggle.In comparis… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
11
0

Year Published

1996
1996
2013
2013

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 16 publications
(11 citation statements)
references
References 9 publications
0
11
0
Order By: Relevance
“…Social research based on Heider's [3] attribution theory can be generalized to discern four attributions for poverty, these being individualist, structuralist, fatalist [1,4] , and cultural [5,6] . Heider [3] attribution theory discerned between internal and external attribution types.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Social research based on Heider's [3] attribution theory can be generalized to discern four attributions for poverty, these being individualist, structuralist, fatalist [1,4] , and cultural [5,6] . Heider [3] attribution theory discerned between internal and external attribution types.…”
Section: Introductionmentioning
confidence: 99%
“…External attributions for poverty according to Feagin [1] , are classified under three main schemes. A structural attribution which people externalize responsibility for their own socio-economic state by placing blame on macro-forces as government, public or private institutions [8] , fatalistic attributions as bad luck or destiny [1] and cultural factors [5] as the social system, confessions or ethnicity, Normative and empirical type of studies have used a number of variables that are thought to impact attributions. For instance, some studies, examined the effects of life experiences of groups, distinguished by race, class, gender, age, education, religion, and income [10,13] , political affiliation, dominant ideology [8,9,10,11,12] , political and institutional behavior [12,14] , and cognitive biases among different groups [15,16] .…”
Section: Introductionmentioning
confidence: 99%
“…Although the results portray different scores of poverty from those in previous studies, Lebanese students' structuralistic attributions are explained by the present economic and social crises of their country which transcend a strong orientation of system blame. Recommendations are offered for future crosscultural research on poverty.Research on attribution for poverty has identified four conceptual dimensions for economic failure: individualist, structuralist, fatalist (Feagin, 1972;1975), and cultural dimensions (Harper, 1991). Taken in concert with causal attribution theory (Heider, 1958) the idea of blame is central to understanding the internal SOCIAL…”
mentioning
confidence: 98%
“…Research on attribution for poverty has identified four conceptual dimensions for economic failure: individualist, structuralist, fatalist (Feagin, 1972;1975), and cultural dimensions (Harper, 1991). Taken in concert with causal attribution theory (Heider, 1958) the idea of blame is central to understanding the internal SOCIAL…”
mentioning
confidence: 98%
“…To illustrate, research findings showed the significance of factors such as attributions for poverty, stereotypes, personality traits, and particular belief and value systems in determining public attitudes towards and support for aid to developing countries (Kennedy & Hill, 2010;Paxton & Knack, 2008;Campbell, Carr, & MacLachlan, 2001;Carr & MacLachlan, 1998;Harper, 1991). The other strand of psychological research on aid highlighted the various aspects of the experiences of aid workers, such as factors that affect their psychological illbeing or wellbeing (Vergara & Gardner, 2011;Musa & Hamid, 2008), as well as the psychological and organisational impact of remuneration differences between local and expatriate workers (Carr, McWha, MacLachlan, & Furnham, 2010).…”
Section: Social Psychological Researches On Aidmentioning
confidence: 99%